Jamaica. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The activities carried out by the Jamaica Delegation of 2022 are identified, focus to needs and interests of the country such as; provided technical support to the Jamaica Baptist Union (JBU) Castor Bean Cluster; build the capacity of the region’s cocoa exporting countries to meet regulations on maximum cadmium levels in cocoa beans and products; IICA’s CCBP proposes the transformation of the existing rudimentary composting site at HBG into a sustainable commercial enterprise that will generate an eight-fold increase in the production and sale of quality compost; the regional standard for compost quality has been submitted member states in the CARICOM Single Market Economy; publication of "Jamaica Antimicrobial Resistance Monitoring System for the Food and Agricultural Sector (JARMS)"; IICA continued to build the capacities of local stakeholders in agricultural health and food safety by developing an African swine fever sensitization video and coordinating the participation of local officials in meetings of the Codex Alimentarius and the World Organisation for Animal Health (WOAH/OIE).